BF‐200 ALA凝胶与MAL乳膏治疗BCC的对比. (24th August 2018) - Morton, C.A.; Dominicus, R.; Radny, P.; Dirschka, T.; Hauschild, A.; Reinhold, U.; Aschoff, R.; Ulrich, M.; Keohane, S.; Ekanayake‐Bohlig, S.; Ibbotson, S.; Ostendorf, R.; et al.
Abstract : Linked Article:  Morton et al. Br J Dermatol 2018;179 :309–319